Left ventricular lead position and clinical outcome in the multicenter automatic defibrillator implantation trial-cardiac resynchronization therapy (MADIT-CRT) trial - Singh, Jagmeet P; Klein, Helmut U; Huang, David T; Reek, Sven; Kuniss, Malte; Quesada, Aurelio; Barsheshet, Alon; Cannom, David; Goldenberg, Ilan; McNitt, Scott; Daubert, James P; Zareba, Wojciech; et al. (Circulation (New York, N.Y.), 2011)
An important determinant of successful cardiac resynchronization therapy for heart failure is the position of the left ventricular (LV) pacing lead. The aim of this study was to analyze the impact of the LV lead position on outcome in patients randomized to cardiac resynchronization-defibrillation in the Multicenter Automatic Defibrillator Implantation Trial-Cardiac Resynchronization Therapy (MADIT-CRT) study. The location of the LV lead was assessed by means of coronary venograms and chest x-rays recorded at the time of device implantation. The LV lead location was classified along the short axis into an anterior, lateral, or posterior position and along the long axis into a basal, midventricular, or apical region. The primary end point of MADIT-CRT was heart failure (HF) hospitalization or death, whichever came first. The LV lead position was assessed in 799 patients, (55% patients ≥65 years of age, 26% female, 10% LV ejection fraction ≤25%, 55% ischemic cardiomyopathy, and 71% left bundle-branch block) with a follow-up of 29±11 months. The extent of cardiac resynchronization therapy benefit was similar for leads in the anterior, lateral, or posterior position (P=0.652). The apical lead location compared with leads located in the nonapical position (basal or midventricular region) was associated with a significantly increased risk for heart failure/death (hazard ratio=1.72; 95% confidence interval, 1.09 to 2.71; P=0.019) after adjustment for the clinical covariates. The apical lead position was also associated with an increased risk for death (hazard ratio=2.91; 95% confidence interval, 1.42 to 5.97; P=0.004). LV leads positioned in the apical region were associated with an unfavorable outcome, suggesting that this lead location should be avoided in cardiac resynchronization therapy. Clinical Trial Registration- URL: http://clinicaltrials.gov. Unique identifier: NCT00180271.